ChemInform Abstract: Polyoxometalates as Homogeneous Oxidation Catalysts. Issue 9 (5th March 2013) - Carraro, Mauro; Sartorel, Andrea; Ibrahim, Masooma; Nsouli, Nadeen; Jahier, Claire; Nlate, Sylvain; Kortz, Ulrich; Bonchio, Marcella
Abstract Review: 175 refs.